Analisis Psikologi Sastra Tokoh Utama Pada Novel Dan Hujan Pun Berhenti Karya Farida Susanty (International Forum of Researchers and Lecturers, 2023)
The problem discussed in this study is how the personality of Leo in the novel And the Rain Stops. This study aims to determine the inner conflicts related to personality in the novel Dan Hujan Pun Henti, by Farida Susanty using a literary psychology approach. This type of research is qualitative descriptive research. The source of this research data is the utterances and words contained in the novel Dan Hujan Pun Henti, by Farida Susanty. The data collection techniques used are reading, recording and analyzing. The results of this study stated that the main character Leo in the novel